2002
DOI: 10.1002/mas.10022
|View full text |Cite
|
Sign up to set email alerts
|

Collision‐induced fragmentations of the (M‐H) parent anions of underivatized peptides: An aid to structure determination and some unusual negative ion cleavages

Abstract: This article describes the fundamental cleavage reactions of (M-H)(-) anions of underivatized peptides that contain up to 25 amino acid residues. The experimental observations of these cleavages have been backed up by molecular modeling, generally at the AM1 level of theory. The basic cleavages are the ubiquitous alpha- and beta-backbone cleavage reactions, which provide information similar to that of the B and Y + 2 cleavages of MH(+) ions of peptides. The residues Asp and Asn also effect cleavages of the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
263
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(275 citation statements)
references
References 39 publications
10
263
1
1
Order By: Relevance
“…[20] The evenelectron species [MÀH] À are likely to be responsible for the observed prominent water loss. [18] A radical-initiated mechanism of CO 2 loss from oxidized species, another prominent EDD feature, has been suggested elsewhere. [20] In comparison, CAD of the [MÀH] À ions led to abundant neutral losses (H 2 O and NH 3 ) from both fragments and precursor ions, but no loss of CO 2 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[20] The evenelectron species [MÀH] À are likely to be responsible for the observed prominent water loss. [18] A radical-initiated mechanism of CO 2 loss from oxidized species, another prominent EDD feature, has been suggested elsewhere. [20] In comparison, CAD of the [MÀH] À ions led to abundant neutral losses (H 2 O and NH 3 ) from both fragments and precursor ions, but no loss of CO 2 .…”
Section: Resultsmentioning
confidence: 96%
“…Although a number of recent publications in the scientific literature have shown that useful sequence information can be derived from CAD mass spectra of negative polypeptide ions, [17,18] negative-ion fragmentation is still rarely used in practice. This is because the spectra obtained from negativeion MS/MS experiments are rife with ion peaks resulting from internal fragmentations, extensive side-chain losses, and neutral losses from fragments, and therefore these spectra are not always easy to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that fragmentation of ions of opposite polarity can provide complementary structural information [34]. Interrogating protein or peptide ions of both polarities is seldom performed, however, even when potentially valuable information might be obtained, presumably due to the additional time and experimental effort associated with analysis of the sample in both polarities.…”
Section: Introductionmentioning
confidence: 99%
“…4 In conclusion, guided by the study of Bowie's group on typical fragmentation patterns in negative ion spectra of peptides and proteins, we were able to elucidate the fragmentation pathway of C-peptide with negative ESI and CID monitoring of the doubly charged deprotonated molecule [ Letter to the Editor 3141…”
mentioning
confidence: 99%